Effective Contract in Higher Education: Intentions and Outcomes - M. V. Kurbatova; I. V. Donova (Высшее образование в России)
The issue of the academic contract in the Russian higher education is associated with the salary systems reform in social sector and scientific field according to the adoption of the Decree of the President of the Russian Federation from May 7, 2012 No. 597 “On Measures for the Implementation of the State Social Policy”. Institutional project of the effective contract was aimed to solve two problems. Firstly, to raise the level of wages. Secondly, to its orientation to increase performance (i.e. outcomes-based payment). Over the past ten years in practice an effective contract evolved from innovation to university routine. On the other hand, researchers moved from substantiating approaches and elaborating methodologies to analyzing the experience of implementing an academic contract and then to evaluating its outcomes. The purpose of this study is to show the outcomes of the implementation of the effective contract project in the higher education system in two directions. Firstly, the achievement of target indicators for increasing the level of salaries of university teachers. Secondly, stimulating more efficient activities.Data from the Monitoring of higher education institutions effectiveness in 2021 is used in the study, and it includes data on 1222 universities. There is information on the average salary of university teachers (excluding part-time workers and civil contract staff) for 2020 for each educational institution, as well as on the ratio of teaching staff salary to the average salary in the region’s economy for 2016-2020. It was revealed that the task of introducing an effective contract for the increasing of salaries is generally being fulfilled but with significant difficulties due to the economic factors. The stimulating impact of an effective contract on the activities of university teachers is realized in conjunction with the solution of the tasks of increasing the effectiveness of the functioning of the universities themselves.